Diretrizes para definir atributos valorativos de empreendimentos imobiliários residenciais verticais - Ardel, Juliana Santana (2014)
This study aims at improving and adjusting a methodology that allows the identification of evaluative attributes of multiple floors in residential buildings. The research is based on real estate agents opinion and on users views. It also aims at improving the quality of information about the final customer and providing data to assist those agents involved with planning and designing vertical residential real estate buildings. This is important so the attributes used on projects are consistent with the needs, expectations and desires of the target audience, enabling them to achieve prominence and its subsequent insertion into the property market. To identify and rank evaluative attributes of properties, the study used a methodology based on market research, using a probability sample, in order to validate the research. The sample or target audience was composed by people interested in buying residential properties in vertical buildings in the city of Uberlândia. The development process involved the participation in events related to the housing market of Uberlândia, also defining relevant data for the attributes of building. It was possible to improve the data collection tool and tabulate the data, making them more streamlined and attractive. In addition, it facilitated the understanding of existing evaluative attributes. Finally, the guidelines were described based on the research carried out.